Handbook of creative cities - edited by David Emanuel Andersson (Cheltenham Northampton, 2011)
With the publication of The Rise of the Creative Class by Richard Florida in 2002, the 'creative city' became the new hot topic among urban policy makers, planners and economists. Florida has developed one of three path-breaking theories about the relationship between creative individuals and urban environments. The economist Ake E. Andersson and the psychologist Dean Simonton are the other members of this 'creative troika'. In the Handbook of Creative Cities, Florida, Andersson and Simonton appear in the same volume for the first time. The expert contributors in this timely Handbook extend their insights with a varied set of theoretical and empirical tools. The diversity of the contributions reflect the multidisciplinary nature of creative city theorizing, which encompasses urban economics, economic geography, social psychology, urban sociology, and urban planning. The stated policy implications are equally diverse, ranging from libertarian to social democratic visions of our shared creative and urban future.
Includes bibliographical references and index.
Keywords: City planning